PERBANDINGAN PENGGUNAAN VARIAN PASIR EKS CIREBON-PEMALI DAN VARIAN EKS CIREBON-GUNG SEBAGAI AGREGAT HALUS PADA BETON TERHADAP NILAI KUAT TEKAN BETON - Teguh Haris; Muhamad Yusuf; Listia Ayu Ningrum; Weimintoro (Engineering : Jurnal Bidang Teknik, 2020)
The use of concrete in the construction is very advanced. With the high demand for concrete, it encourages concrete innovation that is able to support the availability of good quality concrete, one of which is concrete composite material innovation. Material innovation aims to compress the price of concrete and increase the economic value of the composite material itself. The research was carried out by comparing two variations of sand composite aggregate, Ex Cirebon-Pemali compared to Ex Cirebon-Gung. The two components in order to a few of sand aggregate variants with the proportion of each sand aggregate variant of 30% -70%, 40% -60%, 50% -50%, 60% -40 % and 70% -30%. The research intended to find the proportion of variants that are able to produce the best compressive strength. From this variant, the compressive strength of 25.46 MPa was produced at 7 day age concrete and 38.52 MPa at 28 day age concrete by the sand of the Cirebon-Pemali variant of 70% -Pemali 30%. And the maximum compressive strength yield of the Ex-Cirebon-Gung Variant is in the 4th variation 60% - 40%, which is 21.17 MPa at 7 day age concrete and 32.05 MPa at 28 day age concrete. The application of the Ex-Cirebon-Pemali variant compared to the Ex-Cirebon-Gung for high-quality concrete cannot reach the quality of concrete designed for concrete fcr 'in the concrete work mixture.